Assessing the Adherence to Guidelines of Media Reporting of Suicide Using a Novel Instrument—the "Risk of Imitative Suicide Scale" (RISc). Issue 3 (8th November 2014) - Nutt, Rachel; Kidd, Brian; Matthews, Keith
<x xml:space="preserve">Abstract</x> Media guidelines for reporting of suicide are considered important in suicide prevention because of the risk of "imitative" suicide. There are currently no established tools for the quantification of quality of reporting. We sought to develop and validate a quality assessment instrument—the Risk of Imitative Suicide Scale (RISc). The RISc appears capable of discriminating reliably between adherent and nonadherent articles. Our data suggest that adherence to guidelines is inconsistent, and there are major differences between web‐based and print media. The RISc could be used to evaluate effectiveness and consistency of media engagement with suicide prevention strategies.